The Charismatic Journey of Mastery Learning. (November 2015) - Inui, Thomas S.
Abstract : A collection of articles in this issue examine the concept of mastery learning, underscoring that our journey is from a 19th-century construct for assuring skill development (i.e., completing a schedule of rotations driven by the calendar) to a 21st-century sequence of learning opportunities focused on acquiring mastery of special key competencies within clerkships or other activities. Mastery learning processes and standards have the potential to clarify learning goals and competency measurement issues in medical education. Although mastery learning methods originally focused on developing learners' competency with skillful procedures, the author of this Commentary posits that mastery learning methods may be usefully applied more extensively to broader domains of skillful practice, especially those practices that can be linked to outcomes of care. The transition to mastery-focused criteria for educational advancement is laudatory, but challenges will be encountered in the journey to mastery education. The author examines several of these potential challenges, including expansion of mastery learning approaches to effective but relational clinician advice-giving and counseling behaviors, developing criteria for choosing critical competencies that can be linked to outcomes, avoiding a excessively fragmented approach to mastery measurement, and dealing with "educational comorbidity."